Cover. (August 2016) - Unknown
Abstract : On the cover : The cover image of a sea snake was taken by Xavier Bonnet on the beach of the islet Améré and is based on the Original Article Phenotypic variation contrasts with genetic homogeneity across scattered sea snake colonies by Nicolas Bech et al., DOI:10.1111/jbi.12735 .